2014
DOI: 10.24059/olj.v18i4.514
|View full text |Cite
|
Sign up to set email alerts
|

Educational Mixology: A Pedagogical Approach to Promoting Adoption of Technology to Support New Learning Models in Health Science Disciplines

Abstract: For disciplines heavily reliant upon traditional classroom teaching, such as medicine and health sciences, incorporating new learning models may pose challenges for students and faculty. In an effort to innovate curricula, better align courses to required student learning outcomes, and address the call to redesign health professions education, Health Sciences Programs at The George Washington University (GW) embarked on two faculty development initiatives to encourage adoption of online, blended, and technolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…In an effort to innovate curricula, better align courses to required student learning outcomes, and address the call to redesign health professions education, Health Sciences Programs at The George Washington University (GWU) embarked on two faculty development initiatives to encourage adoption of online, blended, and technology-enhanced courses. Authors [20] described the Review, Refresh, and Revise (R3) program, which relies on the evidenced-based Quality Matters Higher Education Rubric and resources from the Supported Media for Administration and Teaching (SMART) Lab to develop and promote a pedagogical approach to course redesign. It also presents preliminary data evaluating the programs in terms of faculty satisfaction, student satisfaction, learning outcomes, and learner engagement.…”
Section: Blended Learning and Higher Education Students' Satisfacmentioning
confidence: 99%
“…In an effort to innovate curricula, better align courses to required student learning outcomes, and address the call to redesign health professions education, Health Sciences Programs at The George Washington University (GWU) embarked on two faculty development initiatives to encourage adoption of online, blended, and technology-enhanced courses. Authors [20] described the Review, Refresh, and Revise (R3) program, which relies on the evidenced-based Quality Matters Higher Education Rubric and resources from the Supported Media for Administration and Teaching (SMART) Lab to develop and promote a pedagogical approach to course redesign. It also presents preliminary data evaluating the programs in terms of faculty satisfaction, student satisfaction, learning outcomes, and learner engagement.…”
Section: Blended Learning and Higher Education Students' Satisfacmentioning
confidence: 99%
“…Even when additional frameworks for understanding or improving one or more aspect of online instructor best practices are used, these are most often mentioned as informing a COI theory. For example, problem based learning is a way to "fully embrace online learning environment" and empower learners within a "natural state of learning" in a real world setting in a digital context [4], [5]. The online community is described within the Scholarship of Teaching and Learning (SOTL) as an 'ecological site' which can create diverse online learning spaces for "education in the margins"; allowing the "somewhat disparate and often isolate off-campus student" to feel more a part of the whole [6].…”
Section: Other Ideas Can Lead To a Better Understandingmentioning
confidence: 99%
“…In opposition to these assumptions, McLaughlin et al found that one of the greatest barriers to implementing a successful flipped classroom was the estimate for faculty time and resources (10 (40). These findings suggest that we may vastly underestimate time, social skills, and resources needed to transition from traditional to online learning (47).…”
Section: How Online Learning Is Uniquementioning
confidence: 58%
“…The implementation of online learning is assumed to result in increased faculty and student productivity and flexibility, decreased cost, student-centric teaching, and comparable student achievement (47). In opposition to these assumptions, McLaughlin et al found that one of the greatest barriers to implementing a successful flipped classroom was the estimate for faculty time and resources (10 (40).…”
Section: How Online Learning Is Uniquementioning
confidence: 90%
See 1 more Smart Citation